Neuroinflammation in treated HIV-positive individuals: A TSPO PET study. (12th April 2016) - Vera, Jaime H.; Guo, Qi; Cole, James H.; Boasso, Adriano; Greathead, Louise; Kelleher, Peter; Rabiner, Eugenii A; Kalk, Nicola; Bishop, Courtney; Gunn, Roger N.; Matthews, Paul M.; Winston, Alan
Abstract : Objective: To explore the effects of microglial activation on brain function and structure, and its relationship with peripheral inflammatory markers, in treated, HIV-positive individuals, using in vivo [ 11 C]PBR28 PET (to measure the 18 kDa translocator protein [TSPO]). Methods: Cognitively healthy HIV-positive individuals on suppressive antiretroviral therapy and HIV-negative individuals (controls) underwent brain [ 11 C]PBR28 PET and MRI. HIV-positive patients completed neuropsychological testing and CSF testing for chemokines. The concentration of bacterial ribosomal 16sDNA in plasma was measured as a marker of microbial translocation. Results: HIV-positive individuals showed global increases in TSPO expression compared to controls (corrected p < 0.01), with significant regional increases in the parietal ( p = 0.001) and occipital ( p = 0.046) lobes and in the globus pallidus ( p = 0.035). TSPO binding in the hippocampus, amygdala, and thalamus were associated with poorer global cognitive performance in tasks assessing verbal and visual memory ( p < 0.05). Increased TSPO binding was associated with increased brain white matter diffusion MRI mean diffusivity in HIV-positive individuals, a lower CD4/CD8 ratio, and both high pretreatment HIV RNA and plasma concentration ribosomal 16s DNA ( p < 0.05). Conclusions: Cognitively healthy HIV-positive individuals show evidence for a chronically activated brain innate immune response and elevated blood markers of microbial translocation despite effective control of plasma viremia. Increased brain inflammation is associated with poorer cognitive performance and white matter microstructural pathology, suggesting a possible role in cognitive impairments found in some HIV-positive patients despite effective treatment.